Diagnostic Accuracy of Ottawa Knee Rule for Diagnosis of Fracture in Patients with Knee Trauma; a Systematic Review and Meta-analysis - Seyyed-Morteza Kazemi; Roya Khorram; Ehsan Fayyazishishavan; Reza Amani-Beni; Yas Haririan; Seyed Mehdi Hosseini Khameneh; Erfan Rahmani; Reza Minaei Noshahr; Mahshad Sarikhani; Rana Rahimi; Sara Saeidi; Diba Saeidi; et al. (Archives of Academic Emergency Medicine, 2023)
Introduction: In order to improve the efficacy of requesting knee radiography and reduce unnecessary radiation exposure, some clinical decision rules have been proposed for the assessment of knee injuries. Among them, the Ottawa Knee Rule (OKR) was considered as one of the best guidelines with several validation studies. Therefore, in this meta-analysis, we aimed to investigate the accuracy of OKR for diagnosis of fracture in patients presenting with knee trauma.